2020
DOI: 10.1186/s43058-020-00089-3
|View full text |Cite
|
Sign up to set email alerts
|

Repeated analyses of national clinical audit reports demonstrate improvements in feedback methods

Abstract: Background There is growing interest in the impact of national clinical audit programmes on the quality of healthcare. There is also an evolving evidence-base for enhancing the design and delivery of audit and feedback. We assessed the extent to which a sample of UK national clinical audit feedback reports met a set of good practice criteria over three time points. Methods We undertook three cross-sectional content analyses. We developed good pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…We also identified potential weaknesses in feedback cycles, such as the omission of specific actions plans for improvement and limited demonstration of audit impacts on patient care and outcomes. We have previously demonstrated variations in how feedback is delivered by UK national clinical audit programmes [ 13 ]. This closer analysis and comparison of two audit programmes has highlighted a range of opportunities to improve impacts specific to each programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified potential weaknesses in feedback cycles, such as the omission of specific actions plans for improvement and limited demonstration of audit impacts on patient care and outcomes. We have previously demonstrated variations in how feedback is delivered by UK national clinical audit programmes [ 13 ]. This closer analysis and comparison of two audit programmes has highlighted a range of opportunities to improve impacts specific to each programme.…”
Section: Discussionmentioning
confidence: 99%
“…A repeated analysis of UK national clinical audit reports identified trends towards the use of more effective feedback methods (e.g. greater use of recommendations for action) and identified further opportunities for improvement [ 13 ]. CP-FIT offers a rigorously derived framework for evaluating feedback interventions and explaining their observed or predicted effects [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using survey and patient data report a change in medication use during the pandemic [ 5 , 7 , 8 ]. Changes in service delivery have been monitored through multiple national audits, which often lag considerably behind the real-time [ 9 , 10 ]. There is an urgent need to focus appropriate resources on optimisation of medication dispensing monitoring systems, especially in vulnerable patient groups, for example those receiving immunosuppressive drugs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using survey and patient data, reported an observed change in medication use during the pandemic (5) (6). Changes in service delivery have been monitored through multiple national audits which often lag considerably behind in real-time (7) (8). There is an urgent need to focus appropriate resources on optimisation of medication dispensing monitoring systems, especially in vulnerable patient groups; for example those receiving immunosuppressive drugs (9).…”
Section: Introductionmentioning
confidence: 99%